Amikacin-Fosfomycin at a Five-to-Two Ratio: Characterization of Mutation Rates in Microbial Strains Causing Ventilator-Associated Pneumonia and Interactions with Commonly Used Antibiotics - Montgomery, A. Bruce (American Society for Microbiology, 2014)
The amikacin-fosfomycin inhalation system (AFIS), a combination of antibiotics administered with an in-line nebulizer delivery system, is being developed for adjunctive treatment of ventilator-associated pneumonia (VAP). The in vitro characterization of amikacin-fosfomycin (at a 5:2 ratio) described here included determining resistance selection rates for pathogens that are representative of those commonly associated with VAP (including multidrug-resistant strains) and evaluating interactions with antibiotics commonly used intravenously to treat VAP. Spontaneous resistance to amikacin-fosfomycin (5:2) was not observed for most strains tested (n, 10/14). Four strains had spontaneously resistant colonies (frequencies, 4.25 × 10(−8) to 3.47 × 10(−10)), for which amikacin-fosfomycin (5:2) MICs were 2- to 8-fold higher than those for the original strains. After 7 days of serial passage, resistance (>4-fold increase over the baseline MIC) occurred in fewer strains (n, 4/14) passaged in the presence of amikacin-fosfomycin (5:2) than with either amikacin (n, 7/14) or fosfomycin (n, 12/14) alone. Interactions between amikacin-fosfomycin (5:2) and 10 comparator antibiotics in checkerboard testing against 30 different Gram-positive or Gram-negative bacterial strains were synergistic (fractional inhibitory concentration [FIC] index, ≤0.5) for 6.7% (n, 10/150) of combinations tested. No antagonism was observed. Synergy was confirmed by time-kill methodology for amikacin-fosfomycin (5:2) plus cefepime (against Escherichia coli), aztreonam (against Pseudomonas aeruginosa), daptomycin (against Enterococcus faecalis), and azithromycin (against Staphylococcus aureus). Amikacin-fosfomycin (5:2) was bactericidal at 4-fold the MIC for 7 strains tested. The reduced incidence of development of resistance to amikacin-fosfomycin (5:2) compared with that for amikacin or fosfomycin alone, and the lack of negative interactions with commonly used intravenous antibiotics, further supports the development of AFIS for the treatment of VAP.